Derivasi dan Infleksi Verba Berafiks ‘di-in’ pada Media Sosial X: Kajian Morfologi - Shafa Aura Alifya; Agur Hari Wibowo (Universitas Nahdlatul Wathan Mataram, 2026)
This study examines the use of non-standard verbs with the di-in affix in posts by users of Social Media Platform X as a morphological phenomenon in contemporary Indonesian. The study aims to describe the di-in affixation pattern and explain the morphological processes involved, particularly the distinction between derivation and inflection. The study employs a descriptive qualitative approach grounded in Katamba’s morphological theory and concepts of Indonesian morphology. The research data consists of written posts by Social Media X users containing verbs with the di-in affix. Data were collected using the observe-and-record method and analyzed using the distributional method through the direct element technique, the substitution technique, and the elision technique. The results indicate that the di-in affixation is a productive and systematic non-standard affixation pattern in social media language. The di-in affix can attach to the base forms of verbs, adjectives, and nouns, thereby producing non-standard passive verbs. Morphologically, the di-in affixation is derivational when it causes a change in word class, particularly from nouns and adjectives to verbs, and is inflectional when it merely marks the passive grammatical relation without altering the word class of the verb base. These findings indicate that linguistic variation in social media is not random but follows specific morphological rules. This study is expected to contribute to the development of Indonesian morphological studies and serve as a reference for language learning and linguistic research in the digital age. Keywords: di-in affixation; derivation; inflection; morphology; social media X